Analisis Harga Pokok Produksi Pada Usaha Furniture Mebel Istana Jati Di Pekalongan Lampung Timur - Suryadi, Suryadi; Nasikah, Durotun; Anggraini, Vika Agustin (Jurnal Manajemen DIVERSIFIKASI, 2023)
From the research results, Jati Palace Furniture has not used the right application method so that the cost of production has not been adequate. The purpose of this study was to determine the determination of the cost of production using the full costing method & the variable costing method. In this study, the analytical tool used was the full costing method. & Variable Costing Method. The results show that it is better to use the Variable Costing Method because the cost of the cost of production is lower but the profit earned is high while using the Full Costing Method the cost of the cost of production is higher but the profit earned is lower. Suggestions related to the research This is to apply the cost of the product in determining the selling price of tables, chairs and beds on the Jati Palace Furniture, it is better to use the variable costing method because it is much cheaper and can reduce the cost of correct production costs.